Thomas Aquinas on human nature : a philosophical study of Summa theologiae 1a, 75-89 - Pasnau, Robert (Cambridge University Press, 2002)
Pasnau sets the philosophy in the context of ancient and modern thought, looking at some of the most difficult areas of Aquinas's thought: the relationship of soul to body, workings of sense and intellect, will and passions, and personal identity.